Heterotopic pancreas mimicking gastric cancer: Case report - Küçük, Gültekin Ozan; Durgun, A. Vedat (Cerrahpaşa Medical Journal, 2014)
Heterotopic pancreas is a congenital anomaly defined as pancreatic tissue occurring outside its normal anatomical location. It is often an incidental finding and can be found at different sites in the gastrointestinal system. It can mimic gastric cancer endoscopically. It is usually asymptomatic. In this report, a 48 years old woman with epigastric pain, nausea and vomiting due to ectopic pancreatic tissue in the stomach is described. Although heterotopic pancreas is rare, it should be considered in the differential diagnosis of submucosal gastric tumors.